La música infantil en el desarrollo de la inteligencia emocional de las niñas y niños de 3 a 4 años de la escuela de educación básica 18 de Noviembre ciudad de Loja. Periodo 2014-2015 - Carrion Coronel, Maria Jose (2016)
This research work aims to provide a thorough study of children's music in the development of emotional intelligence of children 3 to 4 years of the School of Basic Education November 18 City Loja Period. 2014-2015. for it has set an overall objective it is the same as contribute to the development of emotional intelligence through children's music for children. scientific method, synthetic analytical, hermeneutical, statistically the same as served effectively help to achieve the proposed goal: During the research the following methods were used. The population was framed in a number of 10 girls and 10 boys for a total of 20. The research development begins with data collection through an observation sheet emotional intelligence applied to children, which they have obtained the following results: 7 children representing (35%) have a high development of emotional intelligence, 9 children representing (45%) have a medium level of development, and 4 children representing (20%) have a development low emotional intelligence. It concludes that children's music is vital in the development of the child, because through it the child can let flow their emotions and bring out the most of your feelings.